Janitor ergonomics and injuries in the safe workload ergonomic exposure project (SWEEP) study. (November 2019) - Schwartz, Adam; Gerberich, Susan G.; Kim, Hyun; Ryan, Andrew D.; Church, Timothy R.; Albin, Thomas J.; McGovern, Patricia M.; Erdman, Arthur E.; Green, Deirdre R.; Arauz, Rony F.
Abstract: Introduction: A Minnesota union identified to researchers at the University of Minnesota a concern relevant to a possible relation between their daily workload and outcome of occupational injuries among a population of janitors. Objective: To assess if the ergonomic workload is related to injuries among janitors. Methods: Following an initial group discussion among janitors, which identified common and hazardous tasks potentially leading to occupational injuries, a questionnaire was developed, pre-tested, and distributed to the janitors. Questions addressed various exposures, including workload, and comprehensive information regarding injury occurrence over two six-month sequential periods (May 2016–October 2016, November 2016–April 2017). Quantitative ergonomic analyses were performed on a sub-group of janitors (n = 30); these included data collection to identify Borg Perceived Exertion (Borg) and Rapid Entire Body Assessment (REBA) scores. Descriptive, multivariable with bias adjustment analyses were conducted on the resulting data. Results: Eight tasks were found to be common for janitors. All average REBA scores for the tasks were identified in the high-risk category. The task of repeatedly emptying small trash cans (<25lb) was significantly related to injuries. Average Borg scores fell between the very light perceived exertion and somewhat difficult perceived exertion categories. Multivariable regression analyses indicated that age-sex-standardized ergonomic workload, measured by task frequencies and REBA or Borg scores, was positively related to injury occurrence. Conclusions: Standardized ergonomic workload was positively related to injury occurrence. This information serves as a basis for further research and potential intervention efforts. Highlights: Average REBA scores for janitorial tasks were identified in the high-risk category. Average Borg scores for janitorial tasks ranged between very light and somewhat difficult perceived exertion categories. The task of repeatedly emptying small trash cans (<25lb) was significantly related to injuries. Multivariable analyses: ergonomic workload (task frequencies and REBA or Borg scores), was positively related to injury.